2018
DOI: 10.26905/jkdp.v22i1.1800
|View full text |Cite
|
Sign up to set email alerts
|

Weak Form Efficiency of the Insurance Industry: Empirical Evidence from Nigeria

Abstract: This paper evaluated the insurance sector of Nigeria Stock Exchange (NSE) for evidence weak-form efficiency using daily returns from January 2009 to February 2016. The study employs descriptive analysis, non-parametric runs test and autocorrelation function as well as Ljung-Box Q statistics in conducting the evaluation. Descriptive statistics of the insurance sector return series showed negative skewness and leptokurtic distribution. Estimates from the Jarque-Bera normality test showed that the insurance secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Onwukwe and Ali [24] investigated market efficiency in the insurance firms quoted in the Nigerian stock exchange, using insurance sector returns from 2009 to 2016 with descriptive analysis, run test and autocorrelation as techniques for the analysis. The normality results from Jarque-Bera indicated non-normal distribution.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Onwukwe and Ali [24] investigated market efficiency in the insurance firms quoted in the Nigerian stock exchange, using insurance sector returns from 2009 to 2016 with descriptive analysis, run test and autocorrelation as techniques for the analysis. The normality results from Jarque-Bera indicated non-normal distribution.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The stock market returns from 1990 to 2010 revealed that, the security market is inefficient in the weak form, the security market returns from 2010 to 2017 revealed the market is efficient in the weak form. Still in the Nigerian stock exchange, [23,24] investigated weak form of market efficiency and found non-random situation. Overall, there has not been consensus as to the intensity of efficiency in the NSE.…”
Section: Introductionmentioning
confidence: 99%
“…Fama (1970) distinguished the market efficiency into three categories: market efficiency in a weak form, market efficiency in a semistrong form and market efficiency in a strong form. The main component to determine the type of efficiency is information (Khajar, 2010;Taungke & Supramono, 2015;Robiyanto, 2017;Onwukwe & Ali, 2018). Market declared as being efficient in a weak form if the price of an existing asset reflects all past information (Supramono, Widhiastuti, & Utami, 2017).…”
Section: |mentioning
confidence: 99%
“…While Jain, Vyas, & Roy (2013) conducted a study on the stock mar-ket in India, Robiyanto (2015) conducted a study on the stock market in ASEAN and the precious metals market, while Dima & Miloº (2009) did their study in the Romanian stock market. The other studies also were done in the bond market, i.e., Robiyanto (2017) and Onwukwe & Ali (2018) reviewing the efficiency of the insurance market in Nigeria.…”
Section: |mentioning
confidence: 99%
See 1 more Smart Citation